ФОНАЦИЯЛЫҚ ПАРАЛИНГВИСТИКАЛЫҚ ҚУРАЛЛАРДЫҢ ЛИНГВОПОЭТИКАЛЫҚ ӘҲМИЙЕТИ - Кдырбаева, У. (FAN va JAMIYAT, 2024)
The article discusses phonational paralinguistic tools, their types, explains them through examples taken from Karakalpak heroic epics, and reveals their linguopoetic significance.